Team of teams : new rules of engagement for a complex world - McChrystal, Stanley A. (Portfolio/Penguin, 2015)
"As commander of Joint Special Operations Command (JSOC), General Stanley McChrystal discarded a century of management wisdom and pivoted from a pursuit of mechanical efficiency to organic adaptability. In this book, he shows how any organization can make the same transition to act like a team of teams -- where small groups combine the freedom to experiment with a relentless drive to share their experience."--